The Conversation Continues with George Soros
Host Dr. Joseph Duffy (Director, U.S. Information Agency) moderates a discussion on open economies and democratic societies with guests Rose Gottemoeller (National Security Council), Penn Kemble (Deputy Director, U.S. Information Agency), George Soros (financier, businessman, philanthropist), and Paul Wolfowitz (National Defense University).